Positive lessons from life - Mittal, Rakesh K. (New Delhi, 1996)
This book is focused on human psychology. Every life is a mix of good and bad experiences, Perhaps both have to co-exit.The author sees life with this attitude and draws positive lessons from all events irrespective of their. Not only this, he is sharing these lessons with others in the form of this book. .
Keywords: Civil servant